Development of a vibration energy harvesting system with amplitude magnification for wide frequency input - Dharmasena, Pussewela Hewage Amindu; Manukid Parnichkun; Mongkol Ekpanyapong; Ricco, Raffaele; AIT Scholarships (Pathum Thani : Asian Institute of Technology, 2024)
In the quest of harnessing renewable energy to power up the world, focus has been put upon vibration energy. Few harvester types are already being tested in this area. One major aspect of vibration energy is the ability to supply power harnessed sustainably to low power electronic devices. The aim of this research is to design and develop a vibration energy harvester with free-impact motion type which has amplitude magnification to increase power generation and to make the harvester function efficiently for a wider frequency range. The relevant simulations were carried out by deriving the mathematical model. The required CAD modelling, PCB design and fabrication was done to make the physical prototype. The systems designed and developed in this thesis; both numerical model and physical model has managed to achieve the expected outcomes. The advantages of having a mechanical amplifier and the free-impact motion are shown by the magnitude gain the system has achieved and it works for the wide frequency range of 0.1 Hz {u2013} 5 Hz. The overall efficiency for the whole frequency range is hovering around 60% while the efficiency is hovering around 80% for low frequency, low amplitude input vibrations.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Mechatronics and Machine Intelligence
Thesis (M. Eng.) - Asian Institute of Technology, 2024
Keywords: Energy harvesting